Relationship between cyber and in-person dating abuse: a systematic review - Rodríguez-deArriba, María-Luisa (2024)
Dating abuse is widely recognized as a public health issue. A relationship between cyber and in-person dating abuse (CDA and IDA) has been established. A systematic review was carried out with the aim of identifying the studies that analyzed the relationship between CDA and IDA. Filtering by keywords that referred to the sentimental relationship, the context (in-person, online), the aggressive behavior and the participants (adolescents and young adults under 30 years of age) in four databases: PubMed, Scopus, Web of Science, and Science Direct. Studies in English, Portuguese and Spanish were included, and were selecting according to the defined inclusion criteria. A total of 35 studies in English, Portuguese or Spanish met the criteria. A great variability in terms of the methodology adopted by the studies to analyze the relationship between the CDA and the IDA was found, as well as a great diversity in terms of the type of analyses and instruments. Studies showed an overlapping between CDA and IDA as well as strong correlates. However, more longitudinal studies are necessary to concluded about temporal relationships. As implications for preventive policies, it is suggested that interventions in dating abuse should consider both online and offline context.